PENGEMBANGAN MEDIA POP UP BOOK MATERI MENGENAL BANGUN RUANG KELAS IV SD Negeri SUMBERASRI 02 KABUPATEN BLITAR - Rizqi Ulfika Rani; Shofi Nur Amalia; Ragil Tri Oktaviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to determine the validity and attractiveness of Pop Up Book media in learning the introduction of building space in class IV. ADDIE model and R&D approach were used in this research. Interviews, observations, and questionnaires were used to collect data from fourth grade students of SDN Sumberasri 02. Linguists, media experts, and material experts evaluated the validity of the media. The material expert's assessment received a score of 97.5%, the linguist received a score of 91%, and the media expert's evaluation received a score of 87.5% with the same category of “Very Valid”. Regarding the attractiveness of the media, students responded with a score of 97% with the category “Very Interesting”.